Identification of histone acetylation markers in human fetal brains and increased H4K5ac expression in neural tube defects. Issue 12 (14th October 2019) - Li, Dan; Wan, Chunlei; Bai, Baoling; Cao, Haiyan; Liu, Changyun; Zhang, Qin
Abstract: Background: Neural tube defects (NTDs) are severe common birth defects that result from a failure in neural tube closure (NTC). Our previous study has shown that decreased histone methylation altered the regulation of genes linked to NTC. However, the effect of alterations in histone acetylation in human fetuses with NTDs, which are another functional posttranslation modification, remains elusive. Thus, we aimed to identify acetylation sites and changes in histone in patients with NTDs. Methods: First, we identified histone acetylation sites between control human embryonic brain tissue and NTDs using Nano‐HPLC‐MS/MS. Next, we evaluated the level of histone acetylation both groups via western blotting (WB). Finally, we used LC‐ESI‐MS and WB to compare whether histone H4 acetylation was different in NTDs. Results: A total of 43 histone acetylation sites were identified in human embryonic brain tissue, which included 16 novel sites. Furthermore, we found an increased histone acetylation and H4K5ac in tissue with NTDs. Conclusion: Our result present a comprehensive map of histone H4 modifications in the human fetal brain. Furthermore, we provide experimental evidence supporting a relationship between histone H4K5ac and NTDs. This offers a new insight into the pathological role of histone modifications in human NTDs. Abstract : A total of 43 histone acetylation sites were identified in human embryonic brain tissue, which included 16 novel sites. Furthermore, we found increased histone acetylation and H4K5ac in tissue with NTDs.